Proposed design scheme of specialized concept store for Joo Ngan Professional Bike Sdn Bhd at Jln Raja Ekram, 30300 Bandar Ipoh, Perak Darul Ridzuan / Ibrahim Mohd Noor - Mohd Noor, Ibrahim (Faculty of Architecture, Planning and Surveying, 2011)
Final student in Diploma Interior Architecture needs to come out with project report in order to understand the whole final project in first stage until final presentation. The final project is proposed new design of Specialized Concept Store for Joo Ngan Profesional Bike Sdn Bhd at 1311N & 1312N Jin Raja Ekram 30300,Bandar Ipoh,Perak. Specialized Concept Store is a special kind of retail category used to describe a store which focus on only one brand. It is to create a new idea towards a lifestyle theme. This concept store also update their items from time to time. Specialized concept store facilitate public especially bike fans to seek various bicycle item that in focusing to own Specialized brand. In Malaysia, there is no stockiest that sells only a product only based on student observation. Apart from that, Specialized provides various and latest bicycle accessories with reasonable price. Furthermore, the simplest step to reduce environmental pollution is by encouraging the public to use bicycle as their transport. By riding bicycle, it could also reduce incidence such as road accidents and also indirectly can help public to do healthy activity by riding bicycle. Apart from that too , can promote sport in bicycle racing and able to produce icon like ( Azizul Hasni Awang ).